2019
DOI: 10.1111/tpj.14441
|View full text |Cite
|
Sign up to set email alerts
|

PRECOCIOUS1 (POCO1), a mitochondrial pentatricopeptide repeat protein affects flowering time in Arabidopsis thaliana

Abstract: Flowering is a vital developmental shift in plants from vegetative to reproductive phase. The timing of this shift is regulated by various linked genetic pathways including environmental cues and internal regulation. Here we report a role for an Arabidopsis gene, AT1G15480, which encodes a P-class pentatricopeptide repeat (PPR) protein, affecting flowering time. We show that AT1G15480 is localized to mitochondria. An AT1G15480 T-DNA insertion line exhibits an early-flowering phenotype, which is quite a rare ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 74 publications
2
25
0
Order By: Relevance
“…Yet, despite their potential importance, the genetic mechanisms underlying cytonuclear interactions remain obscure (Bock, Andrew, & Rieseberg, 2014;Budar & Roux, 2011;Roux et al, 2016;Soltani et al, 2016). A nuclear-encoded pentatricopeptide repeat (PPR) protein, POCO1, has been shown to regulate flowering time in A. thaliana via mitochondrial RNA editing (Emami & Kempken, 2019), suggesting one possible mechanism that could underlie the cytonuclear interaction we have observed.…”
Section: Discussionmentioning
confidence: 94%
“…Yet, despite their potential importance, the genetic mechanisms underlying cytonuclear interactions remain obscure (Bock, Andrew, & Rieseberg, 2014;Budar & Roux, 2011;Roux et al, 2016;Soltani et al, 2016). A nuclear-encoded pentatricopeptide repeat (PPR) protein, POCO1, has been shown to regulate flowering time in A. thaliana via mitochondrial RNA editing (Emami & Kempken, 2019), suggesting one possible mechanism that could underlie the cytonuclear interaction we have observed.…”
Section: Discussionmentioning
confidence: 94%
“…Biological process GO terms related to biotic stresses and defense response such as "glycosyl compound biosynthesis," "response to biotic stimulus," "glycosinolate biosynthetic," and "sulfur compound biosynthesis process" were over-represented in the up-regulated genes of preinflorescence-inflorescence (69 genes) (Additional file 2: Figure S1). The biological process GO terms "cell redox homeostasis," "cellular homeostasis," and "electron transport chain" were enriched in the down-regulated genes of pre-inflorescence-inflorescence (80 genes) (Additional file 2: Figure S1), which may be related to the higher generation of ROS in poco1 [27]. GO enrichment of the up-and down-regulated genes of inflorescence-flowering (338 and 537 genes respectively) (Additional file 2: Figure S1) showed that various stress response-related processes are highly over-represented, which may indicate that different stresses allocate some identical pathways.…”
Section: Analysis Of Differentially Expressed Genesmentioning
confidence: 99%
“…A recent study showed that poco1 carries a T-DNA insertion and was identified to be a homozygous T-DNA insertion mutant [27]. No POCO1 transcript could be identified in poco1 by RT-PCR.…”
Section: Coverage Analysis Confirmed Poco1 T-dna Insertional Mutationmentioning
confidence: 99%
See 2 more Smart Citations